Use of Big Data and Information and Communications Technology in Disasters: An Integrative Review. (26th July 2018) - Freeman, Jeffrey D.; Blacker, Brigette; Hatt, Grace; Tan, Sophia; Ratcliff, Jeremy; Woolf, Thomas B.; Tower, Craig; Barnett, Daniel J.
ABSTRACT: Novel approaches to improving disaster response have begun to include the use of big data and information and communication technology (ICT). However, there remains a dearth of literature on the use of these technologies in disasters. We have conducted an integrative literature review on the role of ICT and big data in disasters. Included in the review were 113 studies that met our predetermined inclusion criteria. Most studies used qualitative methods (39.8%, n=45) over mixed methods (31%, n=35) or quantitative methods (29.2%, n=33). Nearly 80% (n=88) covered only the response phase of disasters and only 15% (n=17) of the studies addressed disasters in low- and middle-income countries. The 4 most frequently mentioned tools were geographic information systems, social media, patient information, and disaster modeling. We suggest testing ICT and big data tools more widely, especially outside of high-income countries, as well as in nonresponse phases of disasters (eg, disaster recovery), to increase an understanding of the utility of ICT and big data in disasters. Future studies should also include descriptions of the intended users of the tools, as well as implementation challenges, to assist other disaster response professionals in adapting or creating similar tools. ( Disaster Med Public Health Preparedness . 2019;13:353–367)